“Have You Ever Seen the Crowd Goin’ Apeshit?”: Disrupting Representations of Animalistic Black Femininity in the French Imaginary - Elodie Silberstein (Humanities, 2019)
16 June 2018. London Stadium. Beyoncé and Jay−Z revealed the premiere of the music video Apeshit. Filmed inside the Louvre Museum in Paris, Beyoncé’s sexual desirability powerfully dialogues with Western canons of high art that have dehumanized or erased the black female body. Dominant tropes have historically associated the black female body with the realm of nature saddled with an animalistic hypersexuality. With this timely release, Apeshit engages with the growing current debate about the ethic of representation of the black subject in European museums. Here, I argue that Beyoncé transcends the tension between nature and culture into a syncretic language to subvert a dominant imperialistic gaze. Drawing on black feminist theories and art history, a formal analysis traces the genealogy and stylistic expression of this vocabulary to understand its political implications. Findings pinpoint how Beyoncé laces past and present, the regal nakedness of her African heritage and Western conventions of the nude to convey the complexity, sensuality, and humanity of black women—thus drawing a critical reimagining of museal practices and enriching the collective imaginary at large.